The Correlation between Students’ Proficiency Score and Their Speaking Ability - Fitri Ayu Wulandari; Bambang Suroso (UM Purwokerto Press, 2023)
This study aims to find out whether there is a correlation between students' EPT scores and their speaking abilities, using the grades of the 5th semester speaking course on students' study result cards or KHS in the English Language Education Study Program at a private university in Purwokerto. The population of this study were 35 students who had been selected based on students who had taken the Speaking in Academic Communication course and had taken the English Proficiency Test. This study was quantitative with data collection using documents and the instrument was human instrument. Based on the analysis, it was found that the correlation value is 0.196. Therefore, there is no significant correlation between students' EPT scores and their speaking.